The Legal Liability of Beauty Clinics in Achieving Justice for Consumers - Yuyut Prayuti; Yeni Arini; Yendi Risdiana (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
Beauty clinics have become an integral part of modern lifestyles, offering aesthetic solutions to enhance self-confidence. However, alongside their popularity, several challenges have emerged, including health risks stemming from hazardous chemicals, malpractice, and inadequate professional competence. Widespread consumerism often overlooks safety aspects, driven by media-induced unrealistic beauty standards. In this context, legal protection for consumers utilizing beauty clinic services is of paramount importance. This study aims to analyze the legal liability of beauty clinics in safeguarding consumer rights, focusing on the application of justice principles. These principles encompass distributive justice, which demands equitable access to services without discrimination, and procedural justice, which ensures transparency and active consumer participation in medical decision-making. Employing a normative juridical method. The findings reveal that, despite existing regulations outlining the obligations of service providers, numerous beauty clinics fail to adhere to established standards. Consumers often suffer harm due to unsafe procedures or the use of unregulated beauty products. In such instances, the BPSK offers an effective mechanism for dispute resolution, providing mediation, conciliation, and arbitration services characterized by low costs and simplified procedures. From the perspective of justice, ensuring that all consumers have equal rights to clear information and safe services is imperative. Furthermore, strengthening consumer involvement in medical decision-making processes is critical to avoiding the dominance of paternalistic relationships between healthcare providers and patients. By enforcing robust legal protections and adopting a holistic approach to justice, consumer protection in beauty clinic services can be significantly enhanced. This would not only mitigate potential harm but also foster a more balanced relationship between consumers and service providers.